Many Everests An Inspiring Journey of Transforming Dreams Into Reality - Kumar Ravindra (Bloomsbury India, 2016)
Many people write about some great principles to be followed in life but only few of them actually practice and live with it. This book is about a person who, coming from a very modest background, has scaled insurmountable odds in his life and finally the Everest, which is considered the highest peak in the world. In this journey he takes us through some principles, which he believes, can help everyone realize their hidden potential and make their dreams come true. Thus, by documenting such real life situations and effect of tricks to successes in such situations in the form of a book, author could reach, penetrate, motivate and improve the lives of people from a wider section of society. The author shares the trick(s) with the readers and explains them in details about its effectiveness in different situations of life and how this technique works well in different situations to bring great successes in life as well as to come out of hopeless situations of multiple failures.